Local externalization of phosphatidylserine mediates developmental synaptic pruning by microglia - Scott‐Hewitt, Nicole; Perrucci, Fabio; Morini, Raffaella; Erreni, Marco; Mahoney, Matthew; Witkowska, Agata; Carey, Alanna; Faggiani, Elisa; Schuetz, Lisa Theresia; Mason, Sydney; Tamborini, Matteo; Bizzotto, Matteo; et al. (The EMBO journal, 2020)
Neuronal circuit assembly requires the fine balance between synapse formation and elimination. Microglia, through the elimination of supernumerary synapses, have an established role in this process. While the microglial receptor TREM2 and the soluble complement proteins C1q and C3 are recognized as key players, the neuronal molecular components that specify synapses to be eliminated are still undefined. Here, we show that exposed phosphatidylserine (PS) represents a neuronal “eat‐me” signal involved in microglial‐mediated pruning. In hippocampal neuron and microglia co‐cultures, synapse elimination can be partially prevented by blocking accessibility of exposed PS using Annexin V or through microglial loss of TREM2. In vivo , PS exposure at both hippocampal and retinogeniculate synapses and engulfment of PS‐labeled material by microglia occurs during established developmental periods of microglial‐mediated synapse elimination. Mice deficient in C1q, which fail to properly refine retinogeniculate connections, have elevated presynaptic PS exposure and reduced PS engulfment by microglia. These data provide mechanistic insight into microglial‐mediated synapse pruning and identify a novel role of developmentally regulated neuronal PS exposure that is common among developing brain structures. Synopsis Microglia help refine developing neural circuits through the elimination of supernumerary synapses. Here we show that exposed phosphatidylserine on pre‐ and postsynaptic membranes functions as an “eat‐me” signal contributing to microglial‐mediated synapse pruning. Phosphatidylserine exposure at both hippocampal and retinogeniculate synapses coincides with the onset of synapse elimination and PS engulfment by microglia. Microglia‐mediated synapse elimination is dependent on TREM2 and exposed phosphatidylserine in vitro . Exposed phosphatidylserine is developmentally regulated across periods of pruning in both hippocampus and visual system. In vivo developmental phosphatidylserine exposure is not caspase 3‐dependent. Loss of C1q leads to elevated phosphatidylserine‐positive presynaptic inputs and reduced microglia engulfment. Graphical Abstract Exposed phosphatidylserine on pre‐ and postsynaptic membranes functions as an “eat‐me” signal contributing to microglia‐mediated synapse pruning.